1990
DOI: 10.1002/1097-0142(19900401)65:7<1502::aid-cncr2820650709>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic epidural spinal cord compression. Results of treatment and survival

Abstract: All medical records of patients treated for metastatic compression of the spinal cord or cauda equina in the eastern part of Denmark from 1979 through 1985 were reviewed. With regard to treatment response and survival, 345 patients could be evaluated. Carcinoma of the lung (19%), prostate (18%), breast (13%), and kidney (10%) were the most frequent primary malignancies causing spinal compression. The outcome of treatment depended primarily on the patients' condition at the time of diagnosis: 79% of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
4

Year Published

1991
1991
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(86 citation statements)
references
References 22 publications
3
78
1
4
Order By: Relevance
“…and of the ambulatory status before radiotherapy have been previously described for the first course of RT for MSCC. 12,[20][21][22][23] The time to development of motor deficits before radiotherapy is also associated with motor function. 12,24 A slower development of motor deficits (>14 days) represents a slower growing lesion.…”
Section: Discussionmentioning
confidence: 99%
“…and of the ambulatory status before radiotherapy have been previously described for the first course of RT for MSCC. 12,[20][21][22][23] The time to development of motor deficits before radiotherapy is also associated with motor function. 12,24 A slower development of motor deficits (>14 days) represents a slower growing lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies perhaps until the mid-1980s collectively showed that decompressive laminectomy alone did not offer any additional benefit compared to conventional radiotherapy [5][6][7][8]. Then evolved a trend towards posterior decompression combined with stabilisation surgery resulting in improved outcome and survival [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The life expectancy of most MSCC patients is quite short, with reported median survival ranging between 2 and 6 months 10,14,20) . In long-term survivors, local control of MSCC becomes important.…”
Section: Introductionmentioning
confidence: 99%